Teaching business skills to women: Impact of business training on women's microenterprise owners in Vietnam. Issue 4 (1st June 2015) - Raven, Peter; Le, Quan V.
Abstract : Purpose: – There is currently a debate between NGOs and academia on the effectiveness of training microcredit recipients. One side suggests that merely supplying credit will stimulate entrepreneurial business. The other side proposes that training microcredit recipients in business skills will improve business performance and probably have other important effects. This study was undertaken with the cooperation Vietnam Women's Union and PeaceTrees Vietnam. The purpose of this paper is to examine the effects of business training programmes for women microcredit recipients in rural areas of Vietnam. Design/methodology/approach: – Using a questionnaire administered to 120 women business owners in several communes in Quang Tri Province, data were collected in 2012 on their business training programmes, perceptions of their business performance, motivation, factors for success, and several other indicators. Findings: – The findings suggest that business training can improve microenterprise performance and has a number of other positive results, such as increasing motivation, success, and perceptions of entrepreneurs. Research limitations/implications: – The research is limited by the nature of the sample and sample size. Future research should focus on women entrepreneurs in other parts of Vietnam, other developing countries, and on male entrepreneurs, to help understand differences between regions, countries, and gender. Originality/value: – This paper provides empirical evidence to support the argument that business training is effective in improving the performance of microenterprises.